DETERMINAN NILAI PERUSAHAAN: PERAN TAX AVOIDANCE, KINERJA KEUANGAN, DAN GOOD CORPORATE GOVERNANCE PADA PERUSAHAAN CONSUMER NON-CYCLICALS - Zidna Ilma Nafi'a; Henny Wirianata (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2026)
Firm value reflects investors’ perceptions of a company’s performance and future prospects. Companies therefore need to pay attention to factors that may influence firm value, including tax avoidance, financial performance, and Good Corporate Governance (GCG). This study aims to examine the effects of tax avoidance, financial performance, and GCG on firm value in consumer non-cyclicals companies listed on the Indonesia Stock Exchange during 2022–2024. Tax avoidance was measured using the Effective Tax Rate (ETR), financial performance was proxied by Return on Assets (ROA), GCG was represented by institutional ownership, and firm value was measured using Price to Book Value (PBV). This study employed a quantitative approach using secondary data obtained from annual reports and financial statements. The sample was selected through purposive sampling, resulting in 36 companies with 91 observations after outlier elimination. Data were analyzed using panel data regression with the Random Effect Model (REM) in E-Views 12. The results show that tax avoidance and GCG have no significant effect on firm value, while financial performance has a positive and significant effect on firm value. Simultaneously, tax avoidance, financial performance, and GCG significantly affect firm value. These findings indicate that investors in the consumer non-cyclicals sector place greater emphasis on profitability than on tax policies and institutional ownership when assessing firm value.